(untitled) (GAIMS Journal of Medical Sciences, 2024)
Bancroftian filariasis is caused by the filarial parasite Wuchereria Bancrofti and is transmitted by Culexmosquitoes. It is found in tropical and subtropical countries. Traditionally, peripheral blood smears identify this condition by finding microfilaria. Inadvertently found adult worms and microfilaria in fine needle aspiration cytology (FNAC). The disease may be missed in the absence of eosinophilia in a CBC or peripheral blood smear. One must be aware of this possibility. Chronic inflammation and lymphedema lead to lymphatic damage, swelling and elephantiasis of the legs, arms, scrotum, breasts, and vulva.A 29-year-old male patient presented with chief complaints of pain and swelling over the right lower limb for one and a half years. It was reported to be filariasis during laboratory investigations.